The acceptability of nicotine containing products as alternatives to cigarettes: findings from two pilot studies - McNeil Ann; Mortimer Kevin; Li Lin; Borland Ron; King Bill; O'Connor Richard J (BMC, 2011)
Abstract Background This study aimed to explore issues that might impact on the acceptability and feasibility of offering smokers nicotine containing products either to quit nicotine use altogether by using as a short term means of quitting cigarettes or as a longer term substitute. Method Two small pilot studies, one in the UK (n = 34) involving face to face contact and direct provision of the product, the other in Australia (n = 31) conducted remotely with products sent in the mail. Results Nicotine lozenges were the most popular products, but significant minorities liked a smokeless product more. Use stimulated interest in quitting, and although many failed to use all the products provided, most were interested in future use, more often to help quit than as a planned long-term substitute. Conclusions These studies indicate an untapped interest in the use of substitutes to reduce the harmfulness of smoking. Studies of this sort do not inhibit interest in quitting nicotine altogether, and may facilitate it. The greater the range of products on offer, the more smokers are likely to try a product to quit.